Students' Voices on Effective Teaching Methods for Grammar Learning in Peer Tutoring Program - Maria Indah Paskarena; Thomas Wahyu Prabowo Mukti (JEELS (Journal of English Education and Linguistics Studies), 2024)
This research investigated students’ perceptions of tutors’ teaching methods applied in one of grammar tutoring classes in an English Education study program at one of the universities in Yogyakarta.  The students’ preferences on grammar teaching methods were also discovered. This research employed a quantitative approach. Fifty-seven students participated in this study and filled out the questionnaire. Their activities during tutoring program were observed. Then, the interview was used to gather further information. The result of the questionnaire revealed a mean score of four point twenty-nine. It showed that the participants of this study shared their positive perceptions of tutors’ teaching methods in grammar tutoring classes. They felt that the tutors were able to build a comfortable learning experience and motivate them to have a language exposure. Additionally, the students desired to learn grammar by using the audio-lingual method and communicative language teaching (CLT) method. This study implies the need for a well-prepared peer tutoring program to help students effectively. Additionally, the administrators can address individual learning differences and provide insights for improving grammar instructions.